1998
DOI: 10.1111/j.1346-8138.1998.tb02404.x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid Carcinoma of the Skin: Report of a Case

Abstract: We report the histological, immunohistochemical and ultrastructural findings of an exophytic cutaneous tumor composed of a mixture of typical basal cell carcinoma (BCC) and malignant fibrous histiocytoma. Nine previously reported carcinosarcomas of the skin are reviewed. We prefer the term "sarcomatoid carcinoma" for this rare neoplasm. Only the BCC showed a positive immunoreaction to cytokeratin; the sarcomatous component was negative, but it did express vimentin, and, focally, smooth-muscle-specific actin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…In most other cutaneous sarcomatoid carcinomas, however, specific lines of mesenchymal differentiation are not identified and the sarcomatous component resembles atypical fibroxanthoma or high-grade pleomorphic sarcoma. 3,6,14,16,18,19,23,26,33,44 We described some histological findings that have not been reported in the previously published cases of cutaneous sarcomatoid carcinomas. Three of our tumors had predominant malignant giant cell tumor-like tumor components.…”
Section: Discussionmentioning
confidence: 44%
“…In most other cutaneous sarcomatoid carcinomas, however, specific lines of mesenchymal differentiation are not identified and the sarcomatous component resembles atypical fibroxanthoma or high-grade pleomorphic sarcoma. 3,6,14,16,18,19,23,26,33,44 We described some histological findings that have not been reported in the previously published cases of cutaneous sarcomatoid carcinomas. Three of our tumors had predominant malignant giant cell tumor-like tumor components.…”
Section: Discussionmentioning
confidence: 44%
“…The immunophenotypic studies performed in the reported cases are summarized in Table . Immunophenotypically, the basaloid epithelial component marks as expected, with immunoreactivity for cytokeratins, p63, bcl‐2, Ber‐EP4, variable EMA, and negative for mesenchymal and melanocytic markers.…”
Section: Discussionmentioning
confidence: 56%
“…In the reported cases, the epithelial component has been predominantly squamous cell and BCCs, and less frequently adnexal and Merkel cell carcinomas . Including this case, 47 cases of basal cell carcinosarcomas have been reported …”
Section: Discussionmentioning
confidence: 82%
“…This term would be plausible in the presence of a malignant epithelial component, such as BCC and SCC, and a mesenchymal component, such as osteosarcoma, chondrosarcoma and rhabdomyosarcoma. Ríos‐Martín et al 11 . first coined the term sarcomatoid carcinoma of the skin after describing a unique case with features of both AFX and BCC.…”
Section: Discussionmentioning
confidence: 99%